Mode‐converted volcanogenic massive sulphide ore lens reflections in vertical seismic profiles from Flin Flon, Manitoba, Canada. (15th June 2015) - Melanson, D.M.; White, D.J.; Samson, C.; Bellefleur, G.; Schetselaar, E.; Schmitt, D.R.
ABSTRACT: In October 2006, three‐component zero‐offset vertical seismic profile data were acquired from a deviated well in the Flin Flon mining camp in Manitoba, Canada, using a dynamite source. These vertical seismic profile data were processed to reveal reflections originating from the 85.5 Mt Flin Flon‐Callinan‐777 volcanogenic massive sulphide ore system. From drill records, mine plans, surficial maps, and seismic data, 3D voxel models of the local geology and known ore zones were built, which were then used in 3D finite‐difference modelled simulations of the vertical seismic profile surveys. The number of geological units partitioning the model was incrementally increased to study the effects of the massive sulphide ore and the major rock units on the seismic response. The simulations and field data were jointly visualized, and reflections originating at some of the known ore zones were identified. These reflections were observed in each of the three components in both the real field and the forward modelled data and indicate a strong mode‐converted component of the reflected wavefield.